Combined role of vitamin D status and CYP24A1 in the transition to systemic lupus erythematosus. Issue 1 (9th June 2016) - Young, Kendra A; Munroe, Melissa E; Guthridge, Joel M; Kamen, Diane L; Niewold, Timothy B; Gilkeson, Gary S; Weisman, Michael H; Ishimori, Mariko L; Kelly, Jennifer; Gaffney, Patrick M; Sivils, Kathy H; Lu, Rufei; et al.
Abstract : Objective: We examined whether measures of vitamin D were associated with transitioning to systemic lupus erythematosus (SLE) in individuals at risk for SLE. Methods: 436 individuals who reported having a relative with SLE but who did not have SLE themselves were evaluated at baseline and again an average of 6.3 (±3.9) years later. Fifty-six individuals transitioned to SLE (≥4 cumulative American College of Rheumatology criteria). 25-Hydroxyvitamin D (25[OH]D) levels were measured by ELISA. Six single-nucleotide polymorphisms in four vitamin D genes were genotyped. Generalised estimating equations, adjusting for correlation within families, were used to test associations between the vitamin D variables and the outcome of transitioning to SLE. Results: Mean baseline 25[OH]D levels (p=0.42) and vitamin D supplementation (p=0.65) were not different between those who did and did not transition to SLE. Vitamin D deficiency (25[OH]D <20 ng/mL) was greater in those who transitioned compared with those who did not transition to SLE (46% vs 33%, p=0.05). The association between 25[OH]D and SLE was modified by CYP24A1 rs4809959, where for each additional minor allele increased 25[OH]D was associated with decreased SLE risk: zero minor alleles (adjusted OR: 1.03, CI 0.98 to 1.09), one minor allele (adjusted OR: 1.01, CI 0.97 to 1.05) and two minor alleles (adjusted OR: 0.91, CI 0.84 to 0.98). Similarly, vitamin D deficiency significantly increased the risk of transitioning to SLE in those with two minor alleles at rs4809959 (adjusted OR: 4.90, CI 1.33 to 18.04). Conclusions: Vitamin D status and CYP24A1 may have a combined role in the transition to SLE in individuals at increased genetic risk for SLE.